Deadly force - ODonnell, Lawrence (New York William Morrow and Company, Inc., 1983)
The author reveals for the first time the full dimensions of the cover-up by the Boston Police Department. He has studied and written about policeuse of deadly force throughout the country.
Keywords: Biography